Interactions of C+(2PJ) with rare gas atoms: incipient chemical interactions, potentials and transport coefficients - Tuttle, William D.; Thorington, Rebecca L.; Viehland, Larry A.; Breckenridge, W.H.; Wright, Timothy G. (The Royal Society, 2018)
Accurate interatomic potentials were calculated for the interaction of a singly charged carbon cation, C+, with a single rare gas atom, RG (RG = Ne–Xe). The RCCSD(T) method and basis sets of quadruple-ζ and quintuple-ζ quality were employed; each interaction energy was counterpoise corrected and extrapolated to the basis set limit. The lowest C+(2P) electronic term of the carbon cation was considered, and the interatomic potentials calculated for the diatomic terms that arise from these: 2Π and 2Σ+. Additionally, the interatomic potentials for the respective spin-orbit levels were calculated, and the effect on the spectroscopic parameters was examined. In doing this, anomalously large spin-orbit splittings for RG = Ar–Xe were found, and this was investigated using multi-reference configuration interaction calculations. The latter indicated a small amount of RG → C+ electron transfer and this was used to rationalize the observations. This is taken as evidence of an incipient chemical interaction, which was also examined via contour plots, Birge–Sponer plots and various population analyses across the C+-RG series (RG = He–Xe), with the latter showing unexpected results. Trends in several spectroscopic parameters were examined as a function of the increasing atomic number of the RG atom. Finally, each set of RCCSD(T) potentials was employed, including spin-orbit coupling to calculate the transport coefficients for C+ in RG, and the results were compared with the limited available data.